1999
DOI: 10.1097/00000542-199901000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Interaction of Ketamine with Recombinant [micro sign], [small kappa, Greek], and [small delta, Greek] Opioid Receptors Expressed in Chinese Hamster Ovary Cells 

Abstract: Ketamine interacts stereoselectively with recombinant mu and kappa opioid receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(53 citation statements)
references
References 24 publications
3
50
0
Order By: Relevance
“…8,33,34 However, at the concentrations employed in human models, these drugs are not only likely to have an effect on the NMDA receptor system, but are also likely to have relevant effects on several G-protein coupled-receptors (notably D 2 and 5-HT 2 as well as monoamine transporters 15,25 and the opioid receptor system. 35 In fact, more recent studies suggest that ketamine and PCP lead to a state of increased, as opposed to decreased, glutamatergic transmission further calling into question the use of these agents as models of the 'hypoglutamate' hypothesis. 36,37 Ketamine and PCP are more commonly used in animal models to produce a state of hyperlocomotion or disruption of sensorimotor gating.…”
Section: Discussionmentioning
confidence: 99%
“…8,33,34 However, at the concentrations employed in human models, these drugs are not only likely to have an effect on the NMDA receptor system, but are also likely to have relevant effects on several G-protein coupled-receptors (notably D 2 and 5-HT 2 as well as monoamine transporters 15,25 and the opioid receptor system. 35 In fact, more recent studies suggest that ketamine and PCP lead to a state of increased, as opposed to decreased, glutamatergic transmission further calling into question the use of these agents as models of the 'hypoglutamate' hypothesis. 36,37 Ketamine and PCP are more commonly used in animal models to produce a state of hyperlocomotion or disruption of sensorimotor gating.…”
Section: Discussionmentioning
confidence: 99%
“…However, it also has significant affinity for dopamine (DA) (Kapur and Seeman 2002), serotonin (5-HT) (Kapur and Seeman 2002), muscarinic (Hustveit et al 1995) and opioid (Hirota et al 1999;Smith et al 1990) receptors as well as sigma recognition sites (Hustveit et al 1995;Nakao et al 2002) and voltage-gated calcium channels (Wong and Martin 1993). Under some circumstances, it indeed appears to have a greater affinity for D 2 receptors when at a high-affinity state than for the PCP site on the NMDA receptor (Seeman et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These include the opioid system (eg, sigma receptors (Robson et al, 2012)), monoamine transporters (Nishimura et al, 1998), and nucleus accumbens and ventral pallidum serotonergic 5-HT 1B receptors in primates (Yamanaka et al, 2014). With regard to the opioid system, an interaction was observed between ketamine and μ- and κ-opioid receptors (Hirota et al, 1999; Wong et al, 1996). In addition, a preliminary PET study showed lower right habenula, insula, ventrolateral PFC, and dorsolateral PFC (dlPFC) metabolism after ketamine infusion (Carlson et al, 2013); notably, in humans, PET assessment of cerebral glucose metabolism provides a relatively specific proxy measure of glutamatergic neurotransmission.…”
Section: Other Molecular Downstream Targets For Developing Rapid Amentioning
confidence: 99%